Content Analysis of Instagram @sadampermana.w as a Medium for Gender Equality Advocacy - Martabillah, Marissakh Diana; Zahro, Farah Fatimatuz (Jurnal Ilmiah Syi'ar, 2025)
Gender issues remain a problem that must continue to be brought to the attention of society. Gender inequality, discrimination, harassment, and sexual violence are topics that are avoided because they are considered taboo. Moreover, society's stigma against victims of sexual harassment prevents victims from reporting crimes because they are viewed negatively or even blamed for causing the harassment. The patriarchal culture that originated from capitalism, whereby men are more dominant, has created gender inequality in Indonesia that continues to this day. In gender equality, the rights of women and men are equal; neither is higher or lower than the other. Therefore, the purpose of this study is to identify and explain Instagram as a means of conveying issues of gender inequality in the content of the @sadampermana.w account. This study uses descriptive qualitative content analysis of the values of gender inequality conveyed through Instagram content. The primary source of content analysis is @sadampermana.w, while secondary sources come from books, journals, and previous literature that support the research topic. The points that underlie gender inequality according to Mansur Fakih include: 1) stereotypes or negative labeling by society, 2) subordination or distinguishing one entity as higher and less important, 3) marginalization, the attitude of excluding a group, 4) double burden or excessive burden, and 5) sexual violence. The research results of the @sadampermana.w account have voiced the five points of gender inequality through reel content on Instagram.